Eusynnada, a resurrected genus of Ochyromerina (Coleoptera: Curculionidae: Curculioninae: Tychiini), with description of a second species from India and Thailand - Kojima, Hiroaki; Ayri, Shaloo; Ramamurthy, V. V. (Zootaxa, 2016)
Eusynnada is resurrected as a valid genus of Ochyromerina and includes the type species E. plaxoides Heller and a related second new species, E. canariumi sp. nov., from Andaman Island (India) and Thailand.